Hubungan Stunting Terhadap Indeks Pembangunan Manusia Di Provinsi Sulawesi Barat Studi Kasus Enam Kabupaten Di Provisi Sulawesi Barat 2019-2023 - Riadi, Arif; Hastuti, Diah Retno Dwi; Astuty, Sri; Rajab, Abd; rahim, abd (Bisnis-Net, 2025)
This research aims to analyze the relationship between stunting and the Human Development Index (HDI) in West Sulawesi Province, especially in six districts during the 2019-2023 period. Stunting as a chronic health problem affects the quality of human resources and regional development. Data includes stunting indicators, Age Spesific Death Rate (ASDR) mean years schooling (MYS), and gross regional domestic product (GRDP) combined with HDI as the dependent variable. A quantitative approach was used with descriptive analysis and Spearman correlation test using SPSS version 29.The research results show that stunting has a significant relationship with HDI in six districts of West Sulawesi Province. The high prevalence of stunting has been proven to reduce life expectancy, hinder educational attainment, and affect GRDP. Districts with lower stunting prevalence show higher HDI, highlighting the importance of health and education interventions in improving the quality of human resources in these regions. This study also identified that life expectancy and average years of schooling are strong indicators that significantly influence HDI.Keywords: age spesific death rate (ASDR) gross regional domestic product (GRDP) mean years schooling (MYS),